Clear cell sarcoma of kidney: A rare entity - Nirupma Lal; Atin Singhai (Indian Journal of Medical and Paediatric Oncology)
Clear cell sarcoma of the kidney is an uncommon renal neoplasm of childhood. It represents one of the most common unfavorable tumors included in National Wilms′ Tumor Study Group clinical protocols. We came across this rare tumor in a 2-year-old male child. The case report is followed by discussion, stating the differentiating features between Wilms′ and clear cell sarcoma, histological details, treatment, and prognostication.